A Time To Celebrate - Abele, Frances (ARCTIC, 1999)
On April 1, 1999 the map of Canada will change forever. The Northwest Territories will be divided to create Nunavut Territory and the new Northwest Territories in the west. The two new territories are the first new jurisdictions to be created in Canada since Newfoundland joined Confederation half a century ago - and they represent the first change to the map of Canada to result from Aboriginal peoples' political activism. It is a time for celebration and for earnest renewal of efforts to build democratic northern governments that truly reflect the best of the founding traditions of the region. .